Controversial Poetry 1400-1625 - Keßler, Judith; Kundert, Ursula; Oosterman, Johan (Radboud Studies in Humanities, 2020)
How to deal with conflicts? Poetry played a crucial role in dealing with religious and political conflicts from 1400 until 1625. All over Europe there was a lively debate. Controversial poetry presents historical controversies in Latin, Italian, Dutch, German, Scots, and Hungarian poetry.; Readership: Researchers in the fields of Dutch, German, Hungarian, Italian, Latin, Scots, and Comparative Literature; Musicology, History of Song, Media History; Media Theory, Philosophical and psychological Aesthetics; Early Modern Cultural and Political History; Church History, Theology. Musicians, especially of Renaissance and Baroque music. Forschende in den folgenden Feldern: Deutsche, Italienische, Lateinische, Niederländische, Schottische, Ungarische und Vergleichende Literatur; Musikwissenschaft, Geschichte des Lieds, Mediengeschichte; Medientheorie, Philosophische und Psychologische Ästhetik; Kultur- und politische Geschichte der frühen Neuzeit; Kirchengeschichte, Theologie. Musiker*innen, vor allem von Renaissance- und Barock-Musik